The Importance of Understanding Cultural Awareness for Managers in the Hospitality Industry (in Indonesia) - Hera Oktadiana; Rendy Herindra Djauhar (Binus Business Review, 2011)
Cultural awareness is a basic knowledge that each individuality must has. In hotel industry, there are positive advantages that could be reached if a manager could appreciate a cultural, value, attitude differences of each person. This paper adjusts how important the understanding of cultural diversity and pragmatic implementation from several cross cultural communication theory, especially for managers in hotel industry. This paper also describes examples of cultural attitude and habits from some countries that could be refferences in workforce diversity.